2015
DOI: 10.7314/apjcp.2015.16.15.6691
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Sentinel Node in Detecting Lymph Node Metastasis in Primary Endometrial Carcinoma

Abstract: Background: Endometrial carcinoma is the most common gynecological cancer and its treatment is still controversial, especially in its early stages. There are conflicting data about the efficacy of retroperitoneal lymphadenectomy during abdominal hysterectomy and bilateral salpingoophrectomy treatment. Lymphadenectomy carries a risk of severe complications, especially in women with co-morbidities. Selective lymphadenectomy has been widely employed for staging evaluation of endometrial carcinoma because it is si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
3
15
1
Order By: Relevance
“…The intraoperative SLN detection rate in the present series was almost 80%, being slightly lower than the rate observed in previous studies performed with cervical tracer injection in intermediate or high-risk EC, in which the SLN detection rate ranged from 83% to 100% [ 3 4 6 8 18 19 20 21 22 23 24 25 ]. Two studies evaluating the SLN procedure with subserosal injection of blue dye in intermediate and/or high-risk EC patients showed detection rates of 73% and 89% [ 26 27 ]. The decreased overall SLN detection in our series could be explained not only by the site of tracer injection but also by the type of tracer, as indocyanine green (ICG) has shown to provide higher SLN detection rates [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intraoperative SLN detection rate in the present series was almost 80%, being slightly lower than the rate observed in previous studies performed with cervical tracer injection in intermediate or high-risk EC, in which the SLN detection rate ranged from 83% to 100% [ 3 4 6 8 18 19 20 21 22 23 24 25 ]. Two studies evaluating the SLN procedure with subserosal injection of blue dye in intermediate and/or high-risk EC patients showed detection rates of 73% and 89% [ 26 27 ]. The decreased overall SLN detection in our series could be explained not only by the site of tracer injection but also by the type of tracer, as indocyanine green (ICG) has shown to provide higher SLN detection rates [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…a Includes 3 studies comparing ICG and blue dye, 12,22,28 2 comparing radiotracer with/without dye, 57,67 3 comparing cervical vs uterine injection, 41,49,76 5 comparing grade 1 vs grades 2e3, 22,27,29,37,64 and 5 comparing endometrioid and non-endometrioid histology. 22,27,29,37,64 Operating time and adverse events The additional operating time for SLN mapping compared with LND ranged from 3 to 40 minutes (6 studies). 23,28,35,43,44,55 One study reported lower blood loss with SLN mapping compared with LND.…”
Section: Sln Diagnostic Accuracymentioning
confidence: 99%
“…In the studies reporting on adverse events (n ÂŒ 1390 women), 1 patient had an anaphylactic reaction to the blue dye 34 ; no other serious adverse events related to SLN mapping were reported. 11,21,24,26,29,30,33,34,[36][37][38]41,44,46,48,50,52,54,55,59,64,[66][67][68] Seven patients experienced serious complications related to completion LND after SLN mapping (5 lymphoceles, 2 vascular injuries). 30,36,50,[55][56][57][58][59] None of the studies reporting adverse events reported longterm outcomes comparing the risk of lymphedema in patients undergoing either SLN mapping alone or in comparison with complete lymphadenectomy.…”
Section: Sln Diagnostic Accuracymentioning
confidence: 99%
“…Sentinel lymph node (SLN) is the first node receiving lymphatic drainage from the primary tumor, and the pathological status of SLN reflects the overall status of entire lymphatic basin. [10]…”
Section: Introductionmentioning
confidence: 99%
“…Women with negative SLN for metastasis may be managed by SLN biopsy instead of systemic lymphadenectomy. [10]…”
Section: Introductionmentioning
confidence: 99%